High-sensitivity and high-stability composite humidity-sensitive material and preparation method thereof
Patent Information
- Application Number
- CN202611272310.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]为了克服上述的技术问题,本发明的目的在于提供了一种高灵敏度高稳定性复合型湿敏材料及其制备方法,解决了现有的湿敏材料灵敏度低、稳定性差的问题
[0040]本发明的一种高灵敏度高稳定性复合型湿敏材料,通过合成磺化芴基二喹啉吩嗪聚芳醚酮,并与聚醚甲基丙烯酸酯、三乙二醇二甲基丙烯酸酯、多壁碳纳米管复合得到湿敏材料,提升了湿敏传感技术的实用性和可靠性,满足了不同应用场景的需求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of humidity-sensitive materials technology, specifically to a high-sensitivity, high-stability composite humidity-sensitive material and its preparation method. Background Technology
[0002] Humidity-sensitive materials are a class of materials that can sense changes in ambient humidity and convert those changes into measurable signals. The superior properties of these materials enable us to monitor humidity changes more accurately and stably.
[0003] While traditional humidity-sensitive materials exhibit good performance under certain conditions, they face several unresolved problems in practical applications. On one hand, these materials suffer from low sensitivity, affecting the real-time performance of detection; on the other hand, their sensor stability is low, easily impacting measurement accuracy. Therefore, this invention provides a high-sensitivity, high-stability composite humidity-sensitive material and its preparation method, effectively improving its stability in long-term applications. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the present invention aims to provide a high-sensitivity and high-stability composite humidity-sensitive material and its preparation method, which solves the problems of low sensitivity and poor stability of existing humidity-sensitive materials.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] In a first aspect, this application provides a highly sensitive and stable composite humidity-sensitive material, comprising the following parts by weight:
[0007] 40-70 parts of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 10-20 parts of polyether methacrylate, 2-4 parts of triethylene glycol dimethacrylate, 3-4 parts of multi-walled carbon nanotubes, and 0.2-0.4 parts of photoinitiator 819;
[0008] The sulfonated fluorenyl diquinoline phenazine polyarylether ketone is prepared by the following steps:
[0009] Step A1: Add 4-bromo-o-phenylenediamine and dichloromethane to a two-necked flask equipped with a stirrer, stir for 5-10 min, add di-tert-butyl dicarbonate and sodium hydroxide solution, stir for 10-12 h, wash with saturated brine 3-5 times, remove dichloromethane by vacuum distillation, precipitate the solid by shaking with n-hexane, filter, dry the filter residue to obtain di-tert-butyl bromodicarbamate;
[0010]
[0011] Step A2: Add 2,7-dibromo-9H-fluorene, pinacol diboronate, and 1,4-dioxane to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 10-20 min, purge with argon gas, add tetra(triphenylphosphine)palladium and potassium acetate, transfer to an oil bath, stir at 110°C for 6 h, cool, add deionized water, extract three times with dichloromethane, combine the organic phases, wash 3-5 times with saturated brine, dry with anhydrous magnesium sulfate, filter, and distill the filtrate under reduced pressure to remove dichloromethane and 1,4-dioxane. Dry to obtain diboronate-based fluorene.
[0012]
[0013] Step A3: Add 4-bromomethoxybenzene, diboronate fluorene, and 1,4-dioxane to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 10-20 min, purge with argon, add tetra(triphenylphosphine)palladium and potassium acetate, transfer to an oil bath, stir at 110°C for 6-8 h, cool, add dichloromethane and saturated brine, separate the liquids, combine the organic phases, dry with anhydrous magnesium sulfate, filter, concentrate the filtrate under reduced pressure, and purify by silica gel column chromatography using a petroleum ether / ethyl acetate mixture as eluent to obtain methoxyphenylboronate-fluorene.
[0014]
[0015] Step A4: Add methoxyphenylboronic acid fluorene, di-tert-butyl bromide, 1,4-dioxane, and deionized water to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 5-10 min. Add 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride and cesium fluoride, stir for 5-10 min, purge with nitrogen for protection, transfer to an oil bath, stir at 110°C for 6-8 h, cool, add distilled water, and extract with dichloromethane. The organic phases were combined three times, washed 3-5 times with saturated brine, dried with anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure. The filtrate was added to a three-necked flask equipped with a stirrer and a spherical condenser with methanol, and nitrogen gas was introduced for protection. The mixture was stirred for 10-20 min, and concentrated hydrochloric acid was added dropwise for 12-16 h. The pH was adjusted to 7 with saturated sodium carbonate solution, and a solid precipitated. The solid was filtered, and the residue was washed 3-5 times with distilled water and dried to obtain methoxyphenyl-diaminofluorene.
[0016]
[0017] Step A5: Add methoxyphenyl-diaminofluorene, cyclohexanehexanone octahydrate, ferric chloride, and acetic acid to a three-necked flask equipped with a stirrer and a reflux condenser. Stir for 10-20 min, transfer to an oil bath, and react at 100 °C for 8-12 h. Adjust the pH to 7 with saturated sodium carbonate solution, filter, wash the filter residue 3-5 times with deionized water, and dry to obtain trimethoxyphenylfluorene-diquinolinephenazine.
[0018]
[0019] Step A6: Add trimethoxyphenylfluorene-diquinoline phenazine to a four-necked flask equipped with a stirrer, thermometer, and reflux condenser. Purge with nitrogen three times, add dichloromethane, transfer to an ice-water bath, add boron tribromide-dichloromethane solution dropwise at 0°C, stir at 24-26°C for 48 hours, quench with deionized water, adjust pH to 7-8 with saturated sodium bicarbonate solution, precipitate solid, filter, wash the filter residue 5-7 times with distilled water, and dry to obtain trihydroxyphenylfluorene-diquinoline phenazine;
[0020]
[0021] Step A7: Add diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130°C and stir for 1 hour, add sodium carbonate, 4,4'-difluorobenzophenone and trihydroxyphenylfluorene-diquinoline phenazine, react at 170°C for 2 hours, react at 250°C for 1 hour, react at 310°C for 3 hours, add to deionized water and stir, filter, crush the filter residue, wash with boiling acetone, ethanol and distilled water 3-5 times in sequence, dry to obtain fluorene-diquinoline phenazine polyarylether ketone;
[0022] Step A8: Add fluorenyl diquinoline phenazine polyarylether ketone and concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25°C for 30 minutes, then raise the temperature to 40-50°C and react for 4-8 hours. Cool the mixture, add it to ice water and stir. Filter the mixture, wash the residue with deionized water until the washing liquid is neutral, and dry it to obtain sulfonated fluorenyl diquinoline phenazine polyarylether ketone.
[0023] In a preferred embodiment of the present invention, the ratio of 4-bromo-o-phenylenediamine, dichloromethane, di-tert-butyl dicarbonate and sodium hydroxide solution in step A1 is 106.92-320.78 mmol: 200-400 mL: 320.78-641.56 mmol: 160-320 mL.
[0024] In a preferred embodiment of the present invention, the molar concentration of the sodium hydroxide solution in step A1 is 2 mol / L.
[0025] In a preferred embodiment of the present invention, the ratio of 2,7-dibromo-9H-fluorene, pinacol diborate, 1,4-dioxane, tetra(triphenylphosphine)palladium, and potassium acetate in step A2 is 20-40 mmol: 33.6-67.2 mmol: 60-120 mL: 0.63-1.26 mmol: 33.6-67.2 mmol.
[0026] In a preferred embodiment of the present invention, the ratio of 4-bromomethoxybenzene, diboronate fluorene, 1,4-dioxane, tetra(triphenylphosphine)palladium and potassium acetate in step A3 is 20-40 mmol: 20-40 mmol: 200-400 mL: 0.8-1.6 mmol: 28-56 mmol.
[0027] In a preferred embodiment of the present invention, the volume ratio of petroleum ether to ethyl acetate in the petroleum ether / ethyl acetate mixed solvent in step A3 is 10:1.
[0028] In a preferred embodiment of the present invention, the ratio of methoxyphenylboronic acid fluorene, di-tert-butyl bromide, 1,4-dioxane, deionized water, 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride, cesium fluoride, methanol, and concentrated hydrochloric acid in step A4 is 1-2 mmol: 1-2 mmol: 3-6 mL: 3-6 mL: 0.05-0.1 mmol: 1.5-3 mmol: 10-20 mL: 12.56-25.12 mL.
[0029] In a preferred embodiment of the present invention, the molar concentration of the concentrated hydrochloric acid in step A4 is 12 mol / L.
[0030] In a preferred embodiment of the present invention, the ratio of methoxyphenyl-diaminofluorene, cyclohexanehexanone octahydrate, ferric chloride, and acetic acid in step A5 is 3-6 mmol: 3-6 mmol: 0.28-0.56 mmol: 20-40 mL.
[0031] In a preferred embodiment of the present invention, the ratio of the amounts of trimethoxyphenylfluorene-diquinoline phenazine, dichloromethane, and boron tribromide-dichloromethane solution in step A6 is 1.8-3.6 mmol: 20-40 mL: 3.6-7.2 mL.
[0032] In a preferred embodiment of the present invention, the molar concentration of the boron tribromide-dichloromethane solution in step A6 is 1 mol / L.
[0033] In a preferred embodiment of the present invention, the ratio of diphenyl sulfone, sodium carbonate, 4,4'-difluorobenzophenone and trihydroxyphenylfluorene-diquinoline phenazine in step A7 is 217-434g: 0.36-0.72mol: 0.36-0.72mol: 0.24-0.48mol.
[0034] In a preferred embodiment of the present invention, the ratio of fluorenyl diquinoline phenazine polyarylether ketone and concentrated sulfuric acid in step A8 is 1-2g: 20-40mL.
[0035] In a preferred embodiment of the present invention, the concentrated sulfuric acid in step A8 has a mass fraction of 98%.
[0036] Secondly, a method for preparing a highly sensitive and stable composite humidity-sensitive material includes the following steps:
[0037] Step 1: Weigh out 40-70 parts by weight of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 10-20 parts of polyether methacrylate, 2-4 parts of triethylene glycol dimethacrylate, 3-4 parts of multi-walled carbon nanotubes, and 0.2-0.4 parts of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0038] Step 2: Sulfonated fluorenyl diquinoline phenazine polyarylether ketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0039] The beneficial effects of this invention are:
[0040] The present invention discloses a high-sensitivity and high-stability composite humidity-sensitive material, which is obtained by synthesizing sulfonated fluorenyl diquinoline phenazine polyarylether ketone and combining it with polyether methacrylate, triethylene glycol dimethacrylate and multi-walled carbon nanotubes. This improves the practicality and reliability of humidity-sensitive sensing technology and meets the needs of different application scenarios.
[0041] A highly sensitive and stable composite humidity-sensitive material was prepared by first protecting the amino group of 4-bromo-o-phenylenediamine with di-tert-butyl dicarbonate to obtain di-tert-butyl bromodicarbamate. Pinalanoyl diboronate reacted with 2,7-dibromo-9H-fluorene to introduce a borate ester group, yielding diboronate fluorene. 4-bromomethoxybenzene reacted with diboronate fluorene to obtain methoxyphenyl borate-fluorene. After reacting with di-tert-butyl bromodicarbamate, the amino group was deprotected with concentrated hydrochloric acid to obtain methoxyphenyl-diaminofluorene. Methoxyphenyl-diaminofluorene underwent a cyclization reaction with cyclohexanehexadecane octahydrate to obtain trimethoxyphenylfluorene-diquinolinephenazine. Boron tribromide converted the methoxy group to a hydroxyl group to obtain trihydroxyphenylfluorene-diquinolinephenazine. Trihydroxyphenylfluorene-diquinolinephenazine reacted with 4,4'- Difluorobenzophenone undergoes a nucleophilic substitution reaction to generate ether bonds, yielding fluorenyl diquinoline phenazine polyaryletherketone. A sulfonic acid group is then introduced onto the fluorenyl group using concentrated sulfuric acid, resulting in sulfonated fluorenyl diquinoline phenazine polyaryletherketone. The introduction of the sulfonic acid group significantly improves the material's hydrophilicity and accelerates the adsorption / desorption kinetics of water molecules. The fluorenyl and diquinoline phenazine structures enhance charge transport capabilities through π-π conjugation. The electron delocalization properties of the phenazine enhance the material's sensitivity to electrical signals related to humidity changes, while the rigid structure of the fluorenyl group helps maintain the material's structural stability under humidity variations. The aromatic structure of the polyaryletherketone backbone endows the material with excellent chemical stability. Furthermore, polyaryletherketone has a low coefficient of thermal expansion and minimal dimensional change after moisture absorption, avoiding mechanical stress damage caused by expansion / contraction. This results in excellent response performance of the humidity-sensitive material in various humidity sensing applications. Detailed Implementation
[0042] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0043] Example 1:
[0044] This embodiment describes a method for preparing a highly sensitive and stable composite humidity-sensitive material, including the following steps:
[0045] Step A1: Add 106.92 mmol of 4-bromo-o-phenylenediamine and 200 mL of dichloromethane to a two-necked flask equipped with a stirrer, stir for 5 min, add 320.78 mmol of di-tert-butyl dicarbonate and 160 mL of 2 mol / L sodium hydroxide solution, stir for 10 h, wash three times with saturated brine, remove dichloromethane by vacuum distillation, precipitate the solid by shaking with n-hexane, filter, dry the filter residue to obtain di-tert-butyl bromodicarbamate;
[0046] Step A2: 20 mmol of 2,7-dibromo-9H-fluorene, 33.6 mmol of pinacol diboronate, and 60 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was ultrasonically dispersed for 10 min, and then argon gas was introduced for protection. 0.63 mmol of tetra(triphenylphosphine)palladium and 33.6 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 6 h. After cooling, deionized water was added, and the mixture was extracted three times with dichloromethane. The organic phases were combined, washed three times with saturated brine, dried with anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure to remove dichloromethane and 1,4-dioxane. After drying, diboronate fluorene was obtained.
[0047] Step A3: 20 mmol of 4-bromomethoxybenzene, 20 mmol of diboronate fluorene, and 200 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was ultrasonically dispersed for 10 min, and argon gas was introduced for protection. 0.8 mmol of tetrakis(triphenylphosphine)palladium and 28 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 6 h. After cooling, dichloromethane and saturated brine were added. The mixture was separated, and the organic phases were combined and dried with anhydrous magnesium sulfate. The mixture was filtered, and the filtrate was concentrated under reduced pressure. Using a petroleum ether / ethyl acetate mixture as the eluent, the filtrate was purified by silica gel column chromatography to obtain methoxyphenylboronate-fluorene.
[0048] Step A4: Add 1 mmol of methoxyphenylboronic acid fluorene, 1 mmol of di-tert-butyl bromide, 3 mL of 1,4-dioxane, and 3 mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 5 min. Add 0.05 mmol of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride and 1.5 mmol of cesium fluoride. Stir for 5 min, purge with nitrogen, transfer to an oil bath, and stir at 110 °C for 6 h. Cool, add distilled water, and extract three times with dichloromethane. Combine the organic phases, wash three times with saturated brine, dry with anhydrous magnesium sulfate, filter, and distill the filtrate under reduced pressure. Add the filtrate and 10 mL of methanol to a three-necked flask equipped with a stirrer and a spherical condenser. Purge with nitrogen and stir for 10 min. Add 12.56 mL of methanol dropwise. React with 12 mol / L concentrated hydrochloric acid for 12 h, adjust the pH to 7 with saturated sodium carbonate solution, precipitate solid, filter, wash the filter residue with distilled water 3-5 times, dry, and obtain methoxyphenyl-diaminofluorene;
[0049] Step A5: Add 3 mmol of methoxyphenyl-diaminofluorene, 3 mmol of cyclohexanehexanone octahydrate, 0.28 mmol of ferric chloride and 20 mL of acetic acid to a three-necked flask equipped with a stirrer and a reflux condenser. Stir for 10 min, transfer to an oil bath, and react at 100 °C for 8 h. Adjust the pH to 7 with saturated sodium carbonate solution, filter, wash the filter residue three times with deionized water, and dry to obtain trimethoxyphenylfluorene-diquinoline phenazine.
[0050] Step A6: Add 1.8 mmol of trimethoxyphenylfluorene-diquinoline phenazine to a four-necked flask equipped with a stirrer, thermometer, and reflux condenser. Purge the flask three times with nitrogen, add 20 mL of dichloromethane, transfer it to an ice-water bath, and add 3.6 mL of 1 mol / L boron tribromide-dichloromethane solution dropwise at 0 °C. Stir at 24 °C for 48 h, quench with deionized water, adjust the pH to 7 with saturated sodium bicarbonate solution, precipitate a solid, filter, wash the residue five times with distilled water, and dry to obtain trihydroxyphenylfluorene-diquinoline phenazine.
[0051] Step A7: Add 217-g of diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130℃ and stir for 1 hour, add 0.36 mol of sodium carbonate, 0.36 mol of 4,4'-difluorobenzophenone and 0.24 mol of trihydroxyphenylfluorene-diquinoline phenazine, react at 170℃ for 2 hours, at 250℃ for 1 hour and at 310℃ for 3 hours, add to deionized water and stir, filter, crush the residue, wash three times in sequence with boiling acetone, ethanol and distilled water, dry to obtain fluorene-diquinoline phenazine polyarylether ketone;
[0052] Step A8: Add 1g of fluorenyl diquinoline phenazine polyarylether ketone and 20mL of 98% concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25℃ for 30min, then raise the temperature to 40℃ and react for 4h. Cool, add to ice water and stir, filter, wash the filter residue with deionized water until the washing liquid is neutral, and dry to obtain sulfonated fluorenyl diquinoline phenazine polyarylether ketone.
[0053] Step A9: Weigh out 40 parts by weight of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 10 parts of polyether methacrylate, 2 parts of triethylene glycol dimethacrylate, 3 parts of multi-walled carbon nanotubes, and 0.2 parts of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0054] Step A10: Sulfonated fluorenyl diquinoline phenazine polyarylether ketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0055] Example 2:
[0056] This embodiment describes a method for preparing a highly sensitive and stable composite humidity-sensitive material, including the following steps:
[0057] Step A1: Add 160.38 mmol of 4-bromo-o-phenylenediamine and 300 mL of dichloromethane to a two-necked flask equipped with a stirrer, stir for 7 min, add 481.17 mmol of di-tert-butyl dicarbonate and 240 mL of 2 mol / L sodium hydroxide solution, stir for 11 h, wash 4 times with saturated brine, remove dichloromethane by vacuum distillation, precipitate the solid by shaking with n-hexane, filter, dry the filter residue to obtain di-tert-butyl bromodicarbamate;
[0058] Step A2: 30 mmol of 2,7-dibromo-9H-fluorene, 50.4 mmol of pinacol diboronate, and 90 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was ultrasonically dispersed for 15 min, and then argon gas was introduced for protection. 0.945 mmol of tetra(triphenylphosphine)palladium and 50.4 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 6 h. After cooling, deionized water was added, and the mixture was extracted three times with dichloromethane. The organic phases were combined, washed four times with saturated brine, dried with anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure to remove dichloromethane and 1,4-dioxane. After drying, diboronate fluorene was obtained.
[0059] Step A3: 30 mmol of 4-bromomethoxybenzene, 30 mmol of diboronate fluorene, and 300 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was ultrasonically dispersed for 15 min, and then argon gas was introduced for protection. 1.2 mmol of tetrakis(triphenylphosphine)palladium and 42 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 7 h. After cooling, dichloromethane and saturated brine were added. The mixture was separated, and the organic phases were combined and dried with anhydrous magnesium sulfate. The mixture was filtered, and the filtrate was concentrated under reduced pressure. Using a petroleum ether / ethyl acetate mixture as the eluent, the filtrate was purified by silica gel column chromatography to obtain methoxyphenylboronate-fluorene.
[0060] Step A4: Add 1.5 mmol of methoxyphenylboronic acid fluorene, 1.5 mmol of di-tert-butyl bromide, 4.5 mL of 1,4-dioxane, and 4.5 mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 7 min. Add 0.075 mmol of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride and 2.25 mmol of cesium fluoride. Stir for 7 min, purge with nitrogen, transfer to an oil bath, and stir at 110 °C for 7 h. Cool, add distilled water, and extract three times with dichloromethane. Combine the organic phases, wash four times with saturated brine, dry with anhydrous magnesium sulfate, filter, and distill the filtrate under reduced pressure. Add the filtrate and 15 mL of methanol to a three-necked flask equipped with a stirrer and a spherical condenser. Purge with nitrogen and stir for 15 min. Add 18.84 mL of methanol dropwise. The mixture was reacted with 12 mol / L concentrated hydrochloric acid for 14 h, and the pH was adjusted to 7 with saturated sodium carbonate solution. A solid precipitated out, which was filtered. The residue was washed four times with distilled water and dried to obtain methoxyphenyl-diaminofluorene.
[0061] Step A5: Add 4.5 mmol of methoxyphenyl-diaminofluorene, 4.5 mmol of cyclohexanehexanone octahydrate, 0.42 mmol of ferric chloride and 30 mL of acetic acid to a three-necked flask equipped with a stirrer and a reflux condenser. Stir for 15 min, transfer to an oil bath, and react at 100 °C for 10 h. Adjust the pH to 7 with saturated sodium carbonate solution, filter, wash the filter residue four times with deionized water, and dry to obtain trimethoxyphenylfluorene-diquinoline phenazine.
[0062] Step A6: Add 2.7 mmol of trimethoxyphenylfluorene-diquinoline phenazine to a four-necked flask equipped with a stirrer, thermometer, and reflux condenser. Purge the flask three times with nitrogen, add 30 mL of dichloromethane, transfer it to an ice-water bath, and add 5.4 mL of 1 mol / L boron tribromide-dichloromethane solution dropwise at 0 °C. Stir at 25 °C for 48 h, quench with deionized water, adjust the pH to 7 with saturated sodium bicarbonate solution, precipitate a solid, filter, wash the residue 6 times with distilled water, and dry to obtain trihydroxyphenylfluorene-diquinoline phenazine.
[0063] Step A7: Add 325.5g of diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130℃ and stir for 1h, add 0.54mol sodium carbonate, 0.54mol 4,4'-difluorobenzophenone and 0.36mol trihydroxyphenylfluorene-diquinoline phenazine, react at 170℃ for 2h, at 250℃ for 1h and at 310℃ for 3h, add to deionized water and stir, filter, crush the filter residue, wash with boiling acetone, ethanol and distilled water 4 times in sequence, dry to obtain fluorene-diquinoline phenazine polyarylether ketone;
[0064] Step A8: Add 1.5g of fluorenyl diquinoline phenazine polyarylether ketone and 30mL of 98% concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25℃ for 30min, then raise the temperature to 45℃ and react for 6h. Cool, add to ice water and stir, filter, wash the filter residue with deionized water until the washing liquid is neutral, and dry to obtain sulfonated fluorenyl diquinoline phenazine polyarylether ketone.
[0065] Step A9: Weigh out 55 parts by weight of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 15 parts by weight of polyether methacrylate, 3 parts by weight of triethylene glycol dimethacrylate, 3.5 parts by weight of multi-walled carbon nanotubes, and 0.3 parts by weight of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0066] Step A10: Sulfonated fluorenyl diquinoline phenazine polyarylether ketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0067] Example 3:
[0068] This embodiment describes a method for preparing a highly sensitive and stable composite humidity-sensitive material, including the following steps:
[0069] Step A1: Add 320.78 mmol of 4-bromo-o-phenylenediamine and 400 mL of dichloromethane to a two-necked flask equipped with a stirrer, stir for 10 min, add 641.56 mmol of di-tert-butyl dicarbonate and 320 mL of 2 mol / L sodium hydroxide solution, stir for 12 h, wash 5 times with saturated brine, remove dichloromethane by vacuum distillation, shake with n-hexane to precipitate the solid, filter, dry the filter residue to obtain di-tert-butyl bromodicarbamate;
[0070] Step A2: 40 mmol of 2,7-dibromo-9H-fluorene, 67.2 mmol of pinacol diborate, and 120 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was ultrasonically dispersed for 20 min, and then argon gas was introduced for protection. 1.26 mmol of tetra(triphenylphosphine)palladium and 67.2 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 6 h. After cooling, deionized water was added, and the mixture was extracted three times with dichloromethane. The organic phases were combined, washed five times with saturated brine, dried with anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure to remove dichloromethane and 1,4-dioxane. After drying, diborate fluorene was obtained.
[0071] Step A3: 40 mmol of 4-bromomethoxybenzene, 40 mmol of diboronate fluorene, and 400 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was ultrasonically dispersed for 20 min, and then argon gas was introduced for protection. 1.6 mmol of tetrakis(triphenylphosphine)palladium and 56 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 8 h. After cooling, dichloromethane and saturated brine were added. The mixture was separated, and the organic phases were combined and dried with anhydrous magnesium sulfate. The mixture was filtered, and the filtrate was concentrated under reduced pressure. Using a petroleum ether / ethyl acetate mixture as the eluent, the filtrate was purified by silica gel column chromatography to obtain methoxyphenylboronate-fluorene.
[0072] Step A4: Add 2 mmol of methoxyphenylboronic acid fluorene, 2 mmol of di-tert-butyl bromide, 6 mL of 1,4-dioxane, and 6 mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 10 min. Add 0.1 mmol of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride and 3 mmol of cesium fluoride. Stir for 10 min, purge with nitrogen, transfer to an oil bath, and stir at 110 °C for 8 h. Cool, add distilled water, and extract three times with dichloromethane. Combine the organic phases, wash five times with saturated brine, dry with anhydrous magnesium sulfate, filter, and distill the filtrate under reduced pressure. Add the filtrate and 20 mL of methanol to a three-necked flask equipped with a stirrer and a spherical condenser. Purge with nitrogen and stir for 20 min. Add 25.12 mL dropwise. The mixture was reacted with 12 mol / L concentrated hydrochloric acid for 16 h, and the pH was adjusted to 7 with saturated sodium carbonate solution. A solid precipitated out, which was then filtered. The residue was washed with distilled water 3-5 times and dried to obtain methoxyphenyl-diaminofluorene.
[0073] Step A5: Add 6 mmol of methoxyphenyl-diaminofluorene, 6 mmol of cyclohexanehexanone octahydrate, 0.56 mmol of ferric chloride and 40 mL of acetic acid to a three-necked flask equipped with a stirrer and a reflux condenser. Stir for 20 min, transfer to an oil bath, and react at 100 °C for 12 h. Adjust the pH to 7 with saturated sodium carbonate solution, filter, wash the filter residue 5 times with deionized water, and dry to obtain trimethoxyphenylfluorene-diquinoline phenazine.
[0074] Step A6: Add 3.6 mmol of trimethoxyphenylfluorene-diquinoline phenazine to a four-necked flask equipped with a stirrer, thermometer, and reflux condenser. Purge the flask three times with nitrogen, add 40 mL of dichloromethane, transfer it to an ice-water bath, add 7.2 mL of 1 mol / L boron tribromide-dichloromethane solution dropwise at 0 °C, stir at 26 °C for 48 h, quench with deionized water, adjust the pH to 8 with saturated sodium bicarbonate solution, precipitate a solid, filter, wash the filter residue seven times with distilled water, and dry to obtain trihydroxyphenylfluorene-diquinoline phenazine;
[0075] Step A7: Add 434g of diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130℃ and stir for 1h, add 0.72mol sodium carbonate, 0.72mol 4,4'-difluorobenzophenone and 0.48mol trihydroxyphenylfluorene-diquinoline phenazine, react at 170℃ for 2h, at 250℃ for 1h and at 310℃ for 3h, add to deionized water and stir, filter, crush the residue, wash 5 times successively with boiling acetone, ethanol and distilled water, dry to obtain fluorene-diquinoline phenazine polyarylether ketone;
[0076] Step A8: Add 2g of fluorenyl diquinoline phenazine polyarylether ketone and 40mL of 98% concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25℃ for 30min, then raise the temperature to 50℃ and react for 8h. Cool, add to ice water and stir, filter, wash the filter residue with deionized water until the washing liquid is neutral, and dry to obtain sulfonated fluorenyl diquinoline phenazine polyarylether ketone.
[0077] Step A9: Weigh out 70 parts by weight of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 20 parts by weight of polyether methacrylate, 4 parts by weight of triethylene glycol dimethacrylate, 4 parts by weight of multi-walled carbon nanotubes, and 0.4 parts by weight of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0078] Step A10: Sulfonated fluorenyl diquinoline phenazine polyarylether ketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0079] Comparative Example 1:
[0080] This comparative example illustrates a method for preparing a highly sensitive and stable composite humidity-sensitive material, comprising the following steps:
[0081] Step A1: Add 434g of diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130℃ and stir for 1h, add 0.72mol sodium carbonate, 0.72mol 4,4'-difluorobenzophenone and 0.48mol 2,7-dihydroxy-9-fluorenone, react at 170℃ for 2h, at 250℃ for 1h, and at 310℃ for 3h, add to deionized water and stir, filter, crush the residue, wash 5 times successively with boiling acetone, ethanol and distilled water, dry to obtain fluorenyl polyarylether ketone;
[0082] Step A2: Add 2g of fluorenyl diquinoline phenazine polyarylether ketone and 40mL of 98% concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25℃ for 30min, then raise the temperature to 50℃ and react for 8h. Cool, add to ice water and stir, filter, wash the filter residue with deionized water until the washing liquid is neutral, and dry to obtain sulfonated fluorenyl polyarylether ketone.
[0083] Step A3: Weigh out 70 parts by weight of sulfonated fluorene polyarylether ketone, 20 parts by weight of polyether methacrylate, 4 parts by weight of triethylene glycol dimethacrylate, 4 parts by weight of multi-walled carbon nanotubes, and 0.4 parts by weight of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0084] Step A4: Sulfonated fluorene polyaryletherketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0085] Comparative Example 2:
[0086] This comparative example illustrates a method for preparing a highly sensitive and stable composite humidity-sensitive material, comprising the following steps:
[0087] Step A1: Add 320.78 mmol of 4-bromo-o-phenylenediamine and 400 mL of dichloromethane to a two-necked flask equipped with a stirrer, stir for 10 min, add 641.56 mmol of di-tert-butyl dicarbonate and 320 mL of 2 mol / L sodium hydroxide solution, stir for 12 h, wash 5 times with saturated brine, remove dichloromethane by vacuum distillation, shake with n-hexane to precipitate the solid, filter, dry the filter residue to obtain di-tert-butyl bromodicarbamate;
[0088] Step A2: 40 mmol of 1,4-dibromobenzene, 67.2 mmol of pinacol diborate, and 120 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was ultrasonically dispersed for 20 min, and then argon gas was introduced for protection. 1.26 mmol of tetra(triphenylphosphine)palladium and 67.2 mmol of potassium acetate were added, and the mixture was transferred to an oil bath. The mixture was stirred at 110 °C for 6 h, cooled, and deionized water was added. The mixture was extracted three times with dichloromethane. The organic phases were combined, washed five times with saturated brine, dried with anhydrous magnesium sulfate, filtered, and the filtrate was distilled under reduced pressure to remove dichloromethane and 1,4-dioxane. The filtrate was dried to obtain diborate benzene.
[0089] Step A3: 40 mmol of 4-bromomethoxybenzene, 40 mmol of diboronate benzene and 400 mL of 1,4-dioxane were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was ultrasonically dispersed for 20 min, and argon gas was introduced for protection. 1.6 mmol of tetrakis(triphenylphosphine)palladium and 56 mmol of potassium acetate were added. The mixture was transferred to an oil bath and stirred at 110 °C for 8 h. After cooling, dichloromethane and saturated brine were added. The mixture was separated, and the organic phases were combined and dried with anhydrous magnesium sulfate. The mixture was filtered, and the filtrate was concentrated under reduced pressure. Using a petroleum ether / ethyl acetate mixture as the eluent, the filtrate was purified by silica gel column chromatography to obtain methoxyphenylboronate benzene.
[0090] Step A4: Add 2 mmol of methoxyphenylboronic acid ester benzene, 2 mmol of di-tert-butyl bromide dicarboxylate, 6 mL of 1,4-dioxane, and 6 mL of deionized water to a three-necked flask equipped with a stirrer and thermometer. Sonicate for 10 min. Add 0.1 mmol of 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride and 3 mmol of cesium fluoride. Stir for 10 min, purge with nitrogen, transfer to an oil bath, and stir at 110 °C for 8 h. Cool, add distilled water, and extract three times with dichloromethane. Combine the organic phases, wash five times with saturated brine, dry with anhydrous magnesium sulfate, filter, and distill under reduced pressure. Add the filtrate and 20 mL of methanol to a three-necked flask equipped with a stirrer and a spherical condenser. Purge with nitrogen and stir for 20 min. Add 25.12 mL dropwise. The mixture was reacted with 12 mol / L concentrated hydrochloric acid for 16 h, and the pH was adjusted to 7 with saturated sodium carbonate solution. A solid was precipitated, filtered, and the filter residue was washed with distilled water 3-5 times and dried to obtain methoxybenzene-diaminobenzene.
[0091] Step A5: Add 6 mmol of methoxybenzene-diaminobenzene, 6 mmol of cyclohexanehexanone octahydrate, 0.56 mmol of ferric chloride and 40 mL of acetic acid to a three-necked flask equipped with a stirrer and a reflux condenser. Stir for 20 min, transfer to an oil bath, and react at 100 °C for 12 h. Adjust the pH to 7 with saturated sodium carbonate solution, filter, wash the filter residue 5 times with deionized water, and dry to obtain trimethoxybenzene-diquinoline phenazine.
[0092] Step A6: Add 3.6 mmol of trimethoxybenzyl-diquinoline phenazine to a four-necked flask equipped with a stirrer, thermometer, and reflux condenser. Purge the flask three times with nitrogen, add 40 mL of dichloromethane, transfer it to an ice-water bath, add 7.2 mL of 1 mol / L boron tribromide-dichloromethane solution dropwise at 0 °C, stir at 26 °C for 48 h, quench with deionized water, adjust the pH to 8 with saturated sodium bicarbonate solution, precipitate a solid, filter, wash the residue 7 times with distilled water, and dry to obtain trihydroxybenzyl-diquinoline phenazine;
[0093] Step A7: Add 434g of diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130℃ and stir for 1h, add 0.72mol sodium carbonate, 0.72mol 4,4'-difluorobenzophenone and 0.48mol trihydroxybenzene-diquinoline phenazine, react at 170℃ for 2h, at 250℃ for 1h, and at 310℃ for 3h, add to deionized water and stir, filter, crush the filter residue, wash with boiling acetone, ethanol and distilled water 5 times in sequence, dry to obtain diquinoline phenazine polyarylether ketone;
[0094] Step A8: Add 2g of diquinoline phenazine polyarylether ketone and 40mL of 98% concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25℃ for 30min, then raise the temperature to 50℃ and react for 8h. Cool, add to ice water and stir, filter, wash the filter residue with deionized water until the washing liquid is neutral, and dry to obtain sulfonated diquinoline phenazine polyarylether ketone.
[0095] Step A9: Weigh out 70 parts by weight of sulfonated diquinoline phenazine polyarylether ketone, 20 parts by weight of polyether methacrylate, 4 parts by weight of triethylene glycol dimethacrylate, 4 parts by weight of multi-walled carbon nanotubes, and 0.4 parts by weight of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0096] Step A10: Sulfonated diquinoline phenazine polyarylether ketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0097] Comparative Example 3:
[0098] This comparative example illustrates a method for preparing a highly sensitive and stable composite humidity-sensitive material, comprising the following steps:
[0099] Step A1: Add 434g of diphenyl sulfone to a three-necked flask equipped with a thermometer and a stirrer, purge with nitrogen for protection, heat to 130℃ and stir for 1h, add 0.72mol sodium carbonate, 0.72mol 4,4'-difluorobenzophenone and 0.48mol 4,4'-dihydroxybenzophenone, react at 170℃ for 2h, at 250℃ for 1h, and at 310℃ for 3h, add to deionized water and stir, filter, crush the residue, wash 5 times successively with boiling acetone, ethanol and distilled water, dry to obtain polyarylether ketone;
[0100] Step A2: Add 2g of polyarylether ketone and 40mL of 98% concentrated sulfuric acid to a three-necked flask equipped with a thermometer and a stirrer. Maintain the temperature at 25℃ for 30min, then raise the temperature to 50℃ and react for 8h. Cool the mixture, add it to ice water and stir. Filter the mixture, wash the residue with deionized water until the washing liquid is neutral, and dry it to obtain sulfonated polyarylether ketone.
[0101] Step A3: Weigh out 70 parts by weight of sulfonated polyaryletherketone, 20 parts by weight of polyether methacrylate, 4 parts by weight of triethylene glycol dimethacrylate, 4 parts by weight of multi-walled carbon nanotubes, and 0.4 parts by weight of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm;
[0102] Step A4: Sulfonated polyaryletherketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.
[0103] Performance testing:
[0104] The materials from Examples 1-3 and Comparative Examples 1-3 were used to prepare thin films with a thickness of 500 nm. Conductive silver paste was coated on the surface of the thin films at 3 mm intervals as electrodes, and copper wires were led out as conductors. After ultraviolet curing, a humidity sensor was obtained.
[0105] The humidity sensors of Examples 1-3 and Comparative Examples 1-3 were subjected to humidity response tests. The humidity response measurement device included an electrochemical workstation and five humidity bottles containing various saturated salt solutions, providing a series of humidity levels at 25°C: LiCl 11%RH, MgCl2 33%RH, NaBr5 6%RH, NaCl 75%RH and CuSO4 96%RH.
[0106] During the measurement process, the humidity sensor was sealed in a humidity bottle, and its leads were connected to an electrochemical workstation. Once the current value stabilized, the humidity sensor was quickly switched to another humidity bottle. A bias voltage of 10V and a sampling frequency of 100Hz were selected to detect changes in current (I). The response and recovery times were defined as the time intervals during adsorption and desorption processes when the current change reached 90%, respectively.
[0107] The humidity sensors of Examples 1-3 and Comparative Examples 1-3 were placed in petri dishes at room temperature and within a humidity range of 45%-55% for 60 days. The sensing performance was measured at 96% relative humidity on day 1, day 14, and day 60, respectively.
[0108] The humidity sensors of Examples 1-3 and Comparative Examples 1-3 were immersed in distilled water at 25°C for 24 hours, then removed and dried in an oven at 45°C. The current value at 96% relative humidity was measured and compared with the current value before immersion.
[0109]
[0110] Referring to the table above, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the moisture-sensitive material prepared by adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone has good sensitivity and stability.
[0111] Based on the comparison between Example 3 and Comparative Example 1, it can be seen that the humidity-sensitive material prepared by adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone has a higher sensitivity than the humidity-sensitive material prepared by adding sulfonated fluorenyl polyarylether ketone, indicating that adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone can improve the sensitivity of the humidity-sensitive material.
[0112] Based on the comparison between Example 3 and Comparative Example 2, it can be seen that the humidity-sensitive material prepared by adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone has a higher sensitivity than the humidity-sensitive material prepared by adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone, indicating that adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone can improve the sensitivity of the humidity-sensitive material.
[0113] Based on the comparison between Example 3 and Comparative Example 3, it can be seen that the humidity-sensitive material prepared by adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone has a higher sensitivity than the humidity-sensitive material prepared by adding sulfonated polyarylether ketone, indicating that adding sulfonated fluorenyl diquinoline phenazine polyarylether ketone can improve the sensitivity of the humidity-sensitive material.
[0114] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0115] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A high-sensitivity, high-stability composite humidity-sensitive material, characterized in that, Includes the following components by weight: 40-70 parts of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 10-20 parts of polyether methacrylate, 2-4 parts of triethylene glycol dimethacrylate, 3-4 parts of multi-walled carbon nanotubes, and 0.2-0.4 parts of photoinitiator 819; The sulfonated fluorenyl diquinoline phenazine polyarylether ketone is prepared by the following steps: Step A1: React 4-bromo-o-phenylenediamine, dichloromethane, di-tert-butyl dicarbonate and sodium hydroxide solution to obtain di-tert-butyl bromodicarbamate; Step A2: 2,7-Dibromo-9H-fluorene, pinacol diboronate, 1,4-dioxane, tetra(triphenylphosphine)palladium and potassium acetate are reacted to obtain diboronate fluorene; Step A3: React 4-bromomethoxybenzene, diboronate fluorene, 1,4-dioxane, tetra(triphenylphosphine)palladium and potassium acetate to obtain methoxyphenylboronate-fluorene; Step A4: Methoxyphenyl borate-fluorene, di-tert-butyl bromide, 1,4-dioxane, deionized water, 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride and cesium fluoride are reacted with methanol and concentrated hydrochloric acid to obtain methoxyphenyl-diaminofluorene; Step A5: Methoxyphenyl-diaminofluorene, cyclohexanehexane octahydrate, ferric chloride, and acetic acid are reacted to obtain trimethoxyphenylfluorene-diquinolinephenazine; Step A6: Stir the solution of trimethoxyphenylfluorene-diquinolinephenazine, dichloromethane, and boron tribromide-dichloromethane to obtain trihydroxyphenylfluorene-diquinolinephenazine; Step A7: Heat and stir diphenyl sulfone, add sodium carbonate, 4,4'-difluorobenzophenone and trihydroxyphenylfluorene-diquinoline phenazine to react and obtain fluorene-diquinoline phenazine polyarylether ketone; Step A8: Fluorenyl diquinoline phenazine polyarylether ketone is reacted with concentrated sulfuric acid to obtain sulfonated fluorenyl diquinoline phenazine polyarylether ketone.
2. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, In step A1, the ratio of 4-bromo-o-phenylenediamine, dichloromethane, di-tert-butyl dicarbonate, and sodium hydroxide solution is 106.92-320.78 mmol: 200-400 mL: 320.78-641.56 mmol: 160-320 mL; the molar concentration of the sodium hydroxide solution is 2 mol / L.
3. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, The ratio of 2,7-dibromo-9H-fluorene, pinacol diboronate, 1,4-dioxane, tetra(triphenylphosphine)palladium, and potassium acetate in step A2 is 20-40 mmol: 33.6-67.2 mmol: 60-120 mL: 0.63-1.26 mmol: 33.6-67.2 mmol.
4. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, The ratio of 4-bromomethoxybenzene, diboronate fluorene, 1,4-dioxane, tetra(triphenylphosphine)palladium and potassium acetate in step A3 is 20-40 mmol: 20-40 mmol: 200-400 mL: 0.8-1.6 mmol: 28-56 mmol.
5. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, In step A4, the ratio of methoxyphenylboronic acid fluorene, di-tert-butyl bromide, 1,4-dioxane, deionized water, 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride, cesium fluoride, methanol, and concentrated hydrochloric acid is 1-2 mmol: 1-2 mmol: 3-6 mL: 3-6 mL: 0.02-0.04 mmol: 1.5-3 mmol: 10-20 mL: 12.56-25.12 mL; the molar concentration of the concentrated hydrochloric acid is 12 mol / L.
6. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, The ratio of methoxyphenyl-diaminofluorene, cyclohexanehexanone octahydrate, ferric chloride, and acetic acid used in step A5 is 3-6 mmol: 3-6 mmol: 0.28-0.56 mmol: 20-40 mL.
7. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, In step A6, the ratio of the amounts of trimethoxyphenylfluorene-diquinolinephenazine, dichloromethane, and boron tribromide-dichloromethane solution is 1.8-3.6 mmol: 20-40 mL: 3.6-7.2 mL; the molar concentration of the boron tribromide-dichloromethane solution is 1 mol / L.
8. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, The ratio of diphenyl sulfone, sodium carbonate, 4,4'-difluorobenzophenone, and trihydroxyphenylfluorene-diquinoline phenazine in step A7 is 217-434 g: 0.36-0.72 mol: 0.36-0.72 mol: 0.24-0.48 mol.
9. The high-sensitivity, high-stability composite humidity-sensitive material according to claim 1, characterized in that, In step A8, the ratio of fluorenyl diquinoline phenazine polyarylether ketone to concentrated sulfuric acid is 1-2 g: 20-40 mL; the mass fraction of the concentrated sulfuric acid is 98%.
10. A method for preparing a high-sensitivity, high-stability composite humidity-sensitive material, characterized in that, The preparation of the high-sensitivity and high-stability composite humidity-sensitive material as described in any one of claims 1-9 includes the following steps: Step 1: Weigh out 40-70 parts by weight of sulfonated fluorenyl diquinoline phenazine polyarylether ketone, 10-20 parts of polyether methacrylate, 2-4 parts of triethylene glycol dimethacrylate, 3-4 parts of multi-walled carbon nanotubes, and 0.2-0.4 parts of photoinitiator 819, and set aside; wherein, the polyether methacrylate is PEM-1066; the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 1-2 μm; Step 2: Sulfonated fluorenyl diquinoline phenazine polyarylether ketone, polyether methacrylate, triethylene glycol dimethacrylate, multi-walled carbon nanotubes, and photoinitiator 819 are ball-milled and mixed to obtain a highly weather-resistant composite moisture-sensitive material.